Feasibility of Prelithiation in LiFePO4. (9th December 2022) - Cao, Mengyan; Liu, Zepeng; Zhang, Xiao; Yang, Lu; Xu, Shiwei; Weng, Suting; Zhang, Simeng; Li, Xiaoyun; Li, Yejing; Liu, Tongchao; Gao, Yurui; Wang, Xuefeng; et al.
Abstract: Lithium iron phosphate (LiFePO4 ) is widely applied as the cathode material for the energy storage Li‐ion batteries due to its low cost and high cycling stability. However, the low theoretical specific capacity of LiFePO4 makes its initial capacity loss more concerning. Therefore, lithium compensation by way of prelithiation and applications of sacrificial Li‐rich additives in LiFePO4 is imminent in elevating the energy density and/or prolonging the lifetime of the LiFePO4 ‐based Li‐ion batteries (LIBs). Prelithiation in LiFePO4 is herein carried out by electrochemical and chemical methods and its feasibility is proved on the basis of the electrochemical evaluations such as the initial charge capacity and the cycling stability. In addition, the site of the pre‐intercalated Li‐ions is found via comprehensive physical characterizations and the density functional theory (DFT) calculations. These findings open a new avenue for elevating the energy density and/or prolonging the lifetime of the high‐energy‐density batteries. Abstract : Prelithiation in LiFePO4 is proved feasible by chemical and electrochemical ways without degrading its performance. The pre‐intercalated Li‐ions are localized on the octahedral Fe site and the tetrahedral P site. An excess of 25–30 mAh g −1 Li‐ions can be extracted from the prelithiated LiFePO4 for lithium compensation.